An attempt in theorizing the urban design competition through the means of rhetoric - Ganestam, Lisa (2014)
This thesis explores urban design competitions, the rhetoric of it and the underlying processes that control the direction, development and result of the same. The intention is to investigate those motivations and motifs that lies behind the architectural competition process, how the competition process may take place, what actors are involved and if there more to the outcome of a competition than merely the design aspects. The main question becomes; may future trends in urban design and landscape architecture be discovered by investigating the field of urban design competitions?